Efficacy of clomiphene citrate and tamoxifen on pregnancy rates in idiopathic male subfertility: A systematic review and meta-analysis - Shadi Khashaba; Shehab Khashaba; Anil Krishan; Angus Bruce; Abdullatif Almaghlouth; Jason Huang; Mahmoud Mima; Craig Niederberger (Asian Journal of Urology)
Objective: Selective estrogen receptor modulators (SERMs) have demonstrated efficacy in the treatment of hypogonadism in males and male factor infertility. Two SERMs, clomiphene citrate and tamoxifen, are now prescribed for off-label use to treat both conditions in males. However, existing literature compares mixed protocols with active management. We aimed to conduct a meta-analysis to evaluate the effect of clomiphene and tamoxifen versus placebo on natural pregnancy rates. Methods: We conducted a comprehensive systematic review of electronic databases: MEDLINE, PubMed/PMC, EMBASE, CINAHL, Cochrane Central Register of Controlled Trials (CENTRAL), Scopus, Google Scholar, and Web of Science. Articles satisfying all selection criteria were analyzed. The primary outcome was the incidence of pregnancy after receiving the treatment. Secondary outcomes included serum follicle-stimulating hormone, luteinizing hormone, and testosterone levels, and sperm count and motility. We calculated the pooled odds ratio, risk ratio, and risk difference to ascertain possible alterations in the direction of the pooled effect size. Results: Ten randomized controlled trials were ultimately included and underwent data extraction. Clomiphene citrate and placebo groups had similar pregnancy rates (10.4% and 7.1%, respectively; odds ratio 1.30 [95% confidence interval 0.27–6.17]; p=0.74). No meta-analysis could be calculated for pregnancy rates in tamoxifen versus placebo groups. Heterogeneity among the studies of both SERMs ranged from low to high. Conclusion: Although clomiphene citrate and tamoxifen are often used off-label for the treatment of male infertility secondary to hypogonadism, studies of SERMs in the treatment of idiopathic male factor infertility are limited and heterogenous, preventing this meta-analysis from investigating the efficacy of SERMs on male infertility. The effect of clomiphene citrate or tamoxifen on the pregnancy rate remains uncertain.